Microsimulation Model for Prevention and Intervention of Coloretal Cancer in China (MIMIC-CRC): Development, Calibration, Validation, and Application - Lu, Bin; Wang, Le; Lu, Ming; Zhang, Yuhan; Cai, Jie; Luo, Chenyu; Chen, Hongda; Dai, Min (Frontiers in Oncology, 2022)
Introduction: Microsimulation model provides important references for decision-making regarding colorectal cancer (CRC) prevention strategies, yet such well-validated model is scarce in China. Methods: We comprehensively introduce the development of MIcrosimulation Model for prevention and Intervention of Colorectal Cancer in China (MIMIC-CRC). The MIMIC-CRC was firstly constructed to simulate the natural history of CRC based on adenoma-carcinoma pathway. The parameters were calibrated and validated using data from population-based cancer registry data and CRC screening programs. Furthermore, to assess the model’s external validity, we compared the model-derived results to outcome patterns of a sigmoidoscopy screening trial in the UK (UKFSS trial). Finally, we evaluated the application potential of the MIMIC-CRC model in CRC screening by comparing the 8 different strategies. Results: We found that most of the model-predicted colorectal lesion prevalence was within the 95% confidence intervals of observed prevalence in a large population-based CRC screening program in China. In addition, model-predicted sex- and age-specific CRC incidence and mortality were equivalent to the registry-based data. The hazard ratios of model-estimated CRC-related incidence and mortality for sigmoidoscopy screening compared to no screening were 0.60 and 0.51 respectively, which were comparable to the reported results of the UKFSS trial. Moreover, we found that all 8 strategies could reduce CRC incidence and mortality compared to no screening. Conclusions: The well-calibrated and validated MIMIC-CRC model may represent a valid tool to assess the comparative effectiveness of CRC screening strategies and will be useful for further decision-making to CRC prevention.